Pre-Service Teacher Perception Towards English as a Medium of Instruction - Oktavian, Andika Fahmi (RETAIN : Journal of Research in English Language Teaching, 2023)
This study examined pre-service teacher perception towards English as the medium of instruction at 2019 cohort English education UNESA. the goal of this study to know pre-service perception using English as the medium of instruction in classroom. There were 27 pre-service teachers for this study, with following breakdown: 13 male pre-service teacher and 14 female pre-service teachers. This study employed qualitative especially basic interpretative studies. The data was gathered with questionnaire and interview. It was to aimed and determined what the perspective, difficulties, and how to overcome the difficulties. According to data result using English as the medium of instruction has advantages and disadvantages and pre-service teacher need to observe it first what the students need and what the student capable of.